2021
DOI: 10.1002/ctm2.418
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 activation induced by PML‐RARα promotes microRNA 125b‐1 expression and confers resistance to chemotherapy in acute promyelocytic leukemia

Abstract: Dear Editor,Chromosomal translocation is a hallmark of acute myeloid leukemia (AML), often leading to gene rearrangements and expression of a fusion oncoprotein. 1 In this work, we described the fusion oncoprotein promyelocytic leukemia-retinoic acid receptor alpha (PML-RARα) as a new mechanism for nuclear factor erythroid 2 (NF-E2)-related factor 2 (NRF2) activation during leukemogenesis and suggest that PML-RARα-induced NRF2/miR-125b-1 is uniformly important in reactive oxygen species (ROS) detoxification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Jurkat T cells were transfected using the Neon ® Transfection System (Invitrogen) with 100 pmol of oligonucleotides in 10 μl reactions [ 43 45 ]. Briefly, 2 × 10 5 cells were suspended in 100 pmol of oligonucleotides in 10 μl reactions, and each 12-well plate was transfected four times.…”
Section: Methodsmentioning
confidence: 99%
“…Jurkat T cells were transfected using the Neon ® Transfection System (Invitrogen) with 100 pmol of oligonucleotides in 10 μl reactions [ 43 45 ]. Briefly, 2 × 10 5 cells were suspended in 100 pmol of oligonucleotides in 10 μl reactions, and each 12-well plate was transfected four times.…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was performed with a qRT-PCR kit (TIANGEN, Beijing, China), and β-actin was used as an internal control. 24,27 Relative expression levels were calculated as a 2 -ΔΔCt method. The primers for qRT-PCR are shown in Table S2.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…(version:2.0.4). 24 High-quality reads were mapped to the human reference genome (GRCh38), and the expression level of each gene was calculated as fragments per kilobase of exon model per million mapped reads.…”
Section: Transcriptome Sequencingmentioning
confidence: 99%
“…Similarly, Bae et al [ 26 ] reported that sestrins activate Nrf2 by promoting p62-dependent autophagic degradation of Keap1 and prevent oxidative liver damage. Although numerous studies have determined that Nrf2 can be regulated by many proteins in numerous biological processes, such as PML-RAR α , the question of whether it is regulated by STAT6 has not been studied thus far [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%